2008
DOI: 10.1007/s00044-008-9133-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel analogues on the α-carbon of houttuyfonate and SAR analysis of antibacterial activity with MOPAC

Abstract: Three novel a-carbon derivatives of houttuyfonate-HOU-C 8 C 1 , HOU-C 8 C 2 , and HOU-C 8 C 4 -were designed and synthesized, and tested for their in vitro antibacterial activities against seven bacterial strains. A set of molecular properties of houttuyfonate and its five analogues were analyzed by MOPAC. Results indicated that the antibacterial activity of HOU-C 8 C 1 is lower than that of HOU-C 8 . However, among HOU-C 8 C n (n = 1, 2, 4), as the hydrophobicity increased so did the activity, especially agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although antibacterial mechanism of SNH remains unknown, it was indicated that SNH exerted its antimicrobial effect mainly through binding of non-polar tail group to bacterial hydrophobic membrane proteins or cytoplasmic enzymes [18,25,26]. The hydrophobic lipid bilayer of cell membrane might be another target of aliphatic chain of SNH, but it seems that a repulsive force between the negatively charged membrane and the anionic hydrophilic moiety of SNH may weaken the potential interaction [27]. This might be an explanation of higher susceptibility of gram positive bacteria to SNH than gram negative bacteria, which have higher negative charge on the outer membrane due to presence of abundant anion charged phospholipids and lipopolysaccharides [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although antibacterial mechanism of SNH remains unknown, it was indicated that SNH exerted its antimicrobial effect mainly through binding of non-polar tail group to bacterial hydrophobic membrane proteins or cytoplasmic enzymes [18,25,26]. The hydrophobic lipid bilayer of cell membrane might be another target of aliphatic chain of SNH, but it seems that a repulsive force between the negatively charged membrane and the anionic hydrophilic moiety of SNH may weaken the potential interaction [27]. This might be an explanation of higher susceptibility of gram positive bacteria to SNH than gram negative bacteria, which have higher negative charge on the outer membrane due to presence of abundant anion charged phospholipids and lipopolysaccharides [28].…”
Section: Discussionmentioning
confidence: 99%
“…[11] The adducts are not only used extensively in diverse products such as vitamin K 3 [12] and houttuynium sodium bisulfate, [13] but also in purification of thermally unstable aldehydes such as phenylacetaldehyde because aldehyde groups can be easily liberated from the bisulfite adducts when treated with acidic or basic aqueous solution. The high efficacy and ease of purification procedures prompted us to investigate application of bisulfite adducts to synthesize nitriles.…”
Section: Introductionmentioning
confidence: 99%